Teleworking in South America: A legal challenge against covid-19 - Ramírez Velásquez, Joanna Carolina; Tapia Tapia, Héctor Eduardo; Vega Abad, Cesar Remigio; Villagómez, Martha (Revista Venezolana de Gerencia, 2021)
Teleworking is a way of rendering services under a relationship of dependence, outside the usual place of work and with the essential use of technological means. In South America its implementation is regulated in some states by law or ministerial resolutions and in others without specific rule that establishes it. The objective of the present study was to examine the legislation established for the implementation of telework against Covid-19 in South America. The methodology consisted of a bibliographic and documentary review of the literature and legislation established for the implementation of telework. For the collection of information were used databases: Redalyc, Latindex, Scielo, Dialnet, DOAJ, SCOPUS, as well as other national and international official sources. The pandemic caused by the Covid-19 has caused a crisis in the labor market that forces the implementation of teleworking generating urgent governmental pronouncements. It is evident in South America its great momentum as an alternative means to address the socio-labor and economic emergency, some states developed their regulations and others advanced in promoting their practice.